The aesthetics of modernist discourse (a critical vision between formation and philosophy) in the light of the graduation project for a student of the Department of Art Education (mural material as a model) (Journal of the College of Basic Education, 2022)
The modernist aesthetic discourse establishes an epistemological system, as the modernist alphabets are drawn, to the extent that the aesthetic discourse is endowed with its materiality and sensitivity, in a way that initiates the recipient to examine the discourse through the two mechanisms of sensory and imaginative perception, so that the bonds of the process of understanding, reflection, participation, and the relational structures between the recipient and the discourse begin to take upward paths, and the intensity of the bonds is within the limits of the relationship between The discourse and the communicator and between what is perceived and imagined. The unity of the subject lies in its complementarity and functionality of these two elements that complement each other.